Detection of vulnerability attack through wireless network on android platform - Muhamad Izhan Fakri, Imran (2014)
This research is to identify the vulnerability attack that focus on the ARP spoofing attack in the Android platform. This is because each of attacks likes Man-In-The-Middle, Session Hijacking and Password Sniffing are occurring cause of ARP spoofing attack. After that, this research continues with studying about the active technique: ARP request and TCPSYN injection of packet that intend for detecting the ARP spoofing attack. This technique is better than the passive technique that also used for detection of the ARP spoofing. The passive technique is not effective to use because it takes time too long to detect and report the attack. Additionally, if the MAC addresses flooding into the ARP cache on switch with ARP requests and replies may lead to new report tables every time which makes it is unreliable. Next, at the end of this research will develop an Android application for applying the active technique as a method to detect and prevent the ARP spoofing attack on Android smartphone. The Android application will be developed by using Java programming language. The main aim here is that Android application can avoid the attacker steal the Android user's information by launching some attacks that started with the ARP spoofing attack.